2014
DOI: 10.1111/pce.12272
|View full text |Cite
|
Sign up to set email alerts
|

Role of root hydrophobic barriers in salt exclusion of a mangrove plant Avicennia officinalis

Abstract: Salt exclusion at the roots and salt secretion in the leaves were examined in a mangrove, Avicennia officinalis. The nonsecretor mangrove Bruguiera cylindrica was used for comparative study of hydrophobic barrier formation in the roots. Bypass flow was reduced when seedlings were previously treated with high salt concentration. A biseriate exodermis was detected in the salt-treated roots, along with an enhanced deposition of hydrophobic barriers in the endodermis. These barriers reduced Na + loading into the x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(64 citation statements)
references
References 93 publications
(236 reference statements)
0
64
0
Order By: Relevance
“…Also of significance was the induction of casparian strip membrane protein 5 (CASP5). CASPs have been shown to be involved in buildup of the casparian strip [51, 63], which is a barrier to apoplastic flow of solutes to the stellar region of the root and is important in salt stress tolerance [64]. Salt stress often induces osmotic effects that inhibit water uptake by reducing hydraulic conductance [30].…”
Section: Discussionmentioning
confidence: 99%
“…Also of significance was the induction of casparian strip membrane protein 5 (CASP5). CASPs have been shown to be involved in buildup of the casparian strip [51, 63], which is a barrier to apoplastic flow of solutes to the stellar region of the root and is important in salt stress tolerance [64]. Salt stress often induces osmotic effects that inhibit water uptake by reducing hydraulic conductance [30].…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that seed coat suberin also varies in composition with environmental temperature during seed maturation and that suberin remains necessary for the entry into highly dormant states associated with maturation under lower temperature regimes. Temperature has been shown to affect suberin composition in potato (Dean, 1989) and recently was shown to be environmentally plastic in Arabidopsis roots, where its deposition is responsive to the salt content of the growth medium and regulates salt uptake (Baxter et al, 2009;Krishnamurthy et al, 2011Krishnamurthy et al, , 2014Barberon et al, 2016). Thus, it is likely that suberin deposition is responsive to multiple environmental cues.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies (Cheng et al 2010(Cheng et al , 2012a showed that heavy metals such as Zn and Cu could directly promote the levels of lignification within the exodermal cell walls. Similar lignification/suberization thickening could also induced by other toxins, such as excessive salt (Schreiber et al 2005;Krishnamurthy et al 2014), sulfide (Armstrong and Armstrong 2005) and organic acids (Armstrong and Armstrong 2001). All of these anatomical changes were suggested as defence responses to prevent further ingress and the spread of toxins within plants.…”
Section: Discussionmentioning
confidence: 95%
“…A barrier property of the lignified/suberized exodermis has been widely described in the literatures dealing with water transport (Garthwaite et al 2006), ion uptake and penetration (Meyer et al 2011;Krishnamurthy et al 2014), and oxygen dynamics (Armstrong and Wright 1975;Colmer 2003). The properties of the exodermis are strongly affected by its external environmental conditions.…”
Section: Discussionmentioning
confidence: 99%